Opening the black box of students’ text-learning processes: A process mining perspective - Rogiers, Amélie; Merchie, Emmelien; Van Keer, Hilde (Frontline Learning Research, 2020)
The current study uncovers secondary school students’ actual use of text-learning strategies during an individual learning task by means of a concurrent self-reported thinking aloud procedure. Think-aloud data of 51 participants with different learner profiles, distinguished based on a retrospective self-report questionnaire (i.e., 15 integrated strategy users, 15 information organizers, 10 mental learners, and 11 limited strategy users), were analysed by means of educational process mining. Both the frequency of students’ strategy use, as well as the temporal patterns between these strategies were studied. The process mining results clearly demonstrated differences between students with different learner profiles with respect to the frequency of their applied strategies, as well as concerning the sequences wherein strategies were applied throughout the course of students’ text-learning process. The added value of combining both retrospective and concurrent self-report measures of students’ strategies as well as conducting process mining analysis is discussed.